Karakteristik Fisikokimia dan Sifat Fungsional Pati Alami Ubi Kayu Hasil Ekstraksi Secara Sederhana - Satmalawati, Endah M; Paramita, Brigitta L; Nino, Jefrianus (AGRITEKNO: Jurnal Teknologi Pertanian, 2024)
Starch production is one of the post-harvest handling methods for cassava, and the resulting native starch can serve as a basic ingredient in various food industries. Understanding the physicochemical and functional properties of native starch and starch modifications such as profiles, gelatinization, retrogradation of starch paste, and rheological features is necessary to determine the appropriate application of starch in different products. This study aimed to determine cassava starch's characteristics, focusing on its physicochemical and functional properties to provide value. Native starch produced from cassava variety Adira-4 tends to exhibit relatively high viscosity (9084 cP), low solubility (0.4%), fairly low swelling power (35.39%), and low clarity (49.5%). Its brightness level was 84.81%, which was lower than the quality standard set by the Standard Nasional Indonesia (SNI). It also possessed type A crystallinity with more compact properties, limiting its application due to its functional properties.